Descriptive Analysis on Product Design of PT. Yakult Malaysia (Case Study: STIE Student Sutaatmadja Subang) - Wanti Nurila; Kuncorosidi Kuncorosidi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2021)
Product design is a corporate identity which is a characteristic made by the company or differentiating from other products sold in the market so that it can add value to the product itself. Product design can change significantly depending on the company itself, namely by innovating continuously on product designs made with the aim that the products produced can survive and expand in the market. PT. Yakult is a manufacturing company engaged in the production of fermented milk whose products are known by the wider community, namely Yakult. Yakult has spread in several countries, one of which is PT. Yakult in Malaysia is located in Seremban, Negeri Sembilan and produces yakult for all of Malaysia, as well as for export to neighboring countries. The yakult factory in Malaysia produces two yakult products, namely yakult ace and yakult ace light. This study was conducted to analyze descriptively about consumer tastes from the community towards the Yakult packaging design produced by the Yakult Company in Malaysia. The method used is descriptive method. The sample selection was carried out using a non-probability sampling technique (purposive sampling) with a total sample of 104 respondents who were calculated using the Slovin formula. The data used is interval data. Statistical methods for testing data and processing data using SPSS 22 for windows and Microsoft excel. In this study, there are aspects that become assessments, namely: 1). Operational aspects, 2). Aspects of reliability, durability, and dependability, 3). Aesthetic aspects, 4). Production aspect, 5). Economic aspects. The results showed that the respondents agreed or gave a positive response to the five aspects of the assessment of the product design of Yakult Ace and Ace Light.